S-Adenosylmethionine Synthesis Is Regulated by Selective N6-Adenosine Methylation and mRNA Degradation Involving METTL16 and YTHDC1 - Hiroki Shima; Mitsuyo Matsumoto; Yuma Ishigami; Masayuki Ebina; Akihiko Muto; Yuho Sato; Sayaka Kumagai; Kyoko Ochiai; Tsutomu Suzuki; Kazuhiko Igarashi (Cell Reports, 2017)
Summary: S-adenosylmethionine (SAM) is an important metabolite as a methyl-group donor in DNA and histone methylation, tuning regulation of gene expression. Appropriate intracellular SAM levels must be maintained, because methyltransferase reaction rates can be limited by SAM availability. In response to SAM depletion, MAT2A, which encodes a ubiquitous mammalian methionine adenosyltransferase isozyme, was upregulated through mRNA stabilization. SAM-depletion reduced N6-methyladenosine (m6A) in the 3′ UTR of MAT2A. In vitro reactions using recombinant METTL16 revealed multiple, conserved methylation targets in the 3′ UTR. Knockdown of METTL16 and the m6A reader YTHDC1 abolished SAM-responsive regulation of MAT2A. Mutations of the target adenine sites of METTL16 within the 3′ UTR revealed that these m6As were redundantly required for regulation. MAT2A mRNA methylation by METTL16 is read by YTHDC1, and we suggest that this allows cells to monitor and maintain intracellular SAM levels. : Shima et al. find that MAT2A mRNA is stabilized upon depletion of intracellular S-adenosylmethionine (SAM). This regulation involves m6A modification in the 3′ UTR, the m6A writer METTL16, and the reader YTHDC1. Additionally, the authors show that multiple specific sites in hairpin regions of the 3′ UTR are targeted by METTL16. Keywords: cycloleucine, MAT2A, methionine adenosyltransferase, METTL16, methyladenosine, RNA, RNA degradation, S-adenosylmethionine, untranslated region, YTHDC1